A micro-centric network. Post-communist Romanian mainstream and indie publishers of U.S. and Canadian contemporary poetry in translation - Tanasescu, Raluca Andreia (Swedish Journal of Romanian Studies, 2020)
This essay examines the corpus of contemporary American and Canadian poetry translated into Romanian in stand-alone volumes between 1990 and 2017 and argues that translators had a deciding impact on the selection of authors, as well as on the configuration of the overall translation network. Romanian poet-translators engaged in an outward cultural movement that galvanized both their own writing and the national literature in general. In doing so, they developed various types of agency covering a wide range of translating patters, from no agency at all to full self-reliance, and a poetics of fecundity that testifies to their engagement with global events and with the microcosm of local literature. Engendered by an assumed material precariousness and by an overt desire for permanent change and synchronous alignment with world literature, these practices should be seen from a micro-centric perspective, that is, paramount in establishing positive relationships with U.S. and Canadian poetries and energizing the local literary scene, rather than simply reflective of a ‘minor’ mode of existence in the global and geopolitical arenas.